Synergistic photothermal therapy of esophageal cancer using Pt@MOF@PSs nanozymes - Shang, Yuhang; Zhao, Yujie; Ding, Ran; Gao, Xinyue; Li, Qi; Li, Ziyi; An, Xinglan (Frontiers in Bioengineering and Biotechnology, 2026)
Globally, esophageal cancer (EC) is the seventh most commonly diagnosed cancer and the sixth leading cause of cancer-related death. However, its treatment remains challenging due to significant obstacles. Photothermal therapy (PTT), a minimally invasive technique, has emerged as a promising method for tumor ablation. However, its efficacy is limited by low photothermal conversion efficiency and poor tissue penetration. To address these limitations, this study developed a metal-organic framework (MOF)-based nanozyme for the treatment of EC. In this system, the dye IR780, used for photothermal conversion, was encapsulated in liposomes and anchored onto the MOF nanozyme, resulting in a Pt@MOF@PSs construct that improved the aqueous stability of IR780. This multifunctional nanozyme showed tumor-targeting and synergistic therapeutic effects. After passive accumulation in EC tissues, Pt@MOF@PSs suppressed hypoxia and promoted reactive oxygen species (ROS) production by using the high H2O2 levels typical of the tumor microenvironment. The PTT activity of Pt@MOF@PSs was confirmed by its significant temperature increase and upregulation of heat shock protein 70 after irradiation with an 808 nm near-infrared laser. These features facilitated the effective modulation of the resistant tumor microenvironment, induced localized hyperthermia, exerted potent cytotoxicity against esophageal squamous carcinoma cells (ESCs), and suppressed EB tumor progression. These findings highlight Pt@MOF@PSs as a promising therapeutic option, integrating hypoxia relief, ROS generation, and PTT for improved therapeutics against EC.